Stability Analysis of Vehicle Negotiating a Curve in the Plane. (25th December 2013) - Sun, Wencai; Tian, Jingjing; Li, Shiwu; Yang, Zhifa; Ma, Zhengdong
Abstract : The steering stability of vehicle was the most important part of vehicle handling and stability. The stability analysis of vehicle negotiating a curve in the plane was studied through simulation. The vehicle dynamics model used in this paper had two degrees of freedom with nonlinear tire characteristics. When two vehicle state variables, namely, velocity and steering angle, were changed, the GA and phase space analysis were used to compute the equilibrium points and analyze the phase space characteristics of vehicle system. Considering the nonlinear tire characteristic, the working region of tire was figured out and compared, while the vehicle was under different operating conditions. From the analysis results, it could be concluded that working in the nonlinear region of tire characteristic was the ultimate reason of vehicle instability. The knowledge derived from simulation results could dramatically enhance the understanding of stability of the actual vehicle negotiating a curve on an even surface. Such knowledge was a prerequisite for robustly designing the chassis, such as steer-by-wire, which would be the topics of future work.